2023
DOI: 10.1099/mgen.0.000995
|View full text |Cite
|
Sign up to set email alerts
|

Extensive genome analysis identifies novel plasmid families in Clostridium perfringens

Abstract: Globally, the anaerobic bacterium Clostridium perfringens causes severe disease in a wide array of hosts; however, C. perfringens strains are also carried asymptomatically. Accessory genes are responsible for much of the observed phenotypic variation and virulence within this species, with toxins frequently encoded on conjugative plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The newly identified Bcp plasmids contain a novel putative conjugation locus (Bcp) with a sequence like Clostridium botulinum plasmids and contigs that have the same plasmid mobilization gene, mobC and the same zeta toxin-encoding gene as pJGS1984_5. Additionally, these plasmids encode VirB4 homologous proteins and VirD4-like conjugation proteins distinct from the variants encoded by the Tcp and Pcp plasmids [ 20 ].…”
Section: Perfringens Toxins: Biological Properties Function ...mentioning
confidence: 99%
“…The newly identified Bcp plasmids contain a novel putative conjugation locus (Bcp) with a sequence like Clostridium botulinum plasmids and contigs that have the same plasmid mobilization gene, mobC and the same zeta toxin-encoding gene as pJGS1984_5. Additionally, these plasmids encode VirB4 homologous proteins and VirD4-like conjugation proteins distinct from the variants encoded by the Tcp and Pcp plasmids [ 20 ].…”
Section: Perfringens Toxins: Biological Properties Function ...mentioning
confidence: 99%
“…Clostridium perfringens isolates can carry up to 10 plasmids, which significantly influence the pathogenic properties. A study by Gulliver et al [ 77 ] suggested that toxin genes that are known to be responsible for the course of diseases are located on plasmids. The authors characterised these plasmids with a novel apparatus that may contribute to the dissemination of genes within the species and between C. perfringens and other species (specifically C. botulinum ).…”
Section: Clostridium Perfringens —Molecular Diversitymentioning
confidence: 99%